2020
DOI: 10.1002/pol.20200584
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis methods of organic two‐dimensional materials

Abstract: Among various two‐dimensional (2D) materials, organic 2D polymers have attracted much attention, owing to their specific properties, such as lightweight, good flexibility, adjustable structure, and high adaptability. In recent years, more and more scientists have devoted to the research on their structural design, synthesis, characterization, and potential properties. However, in contrast to traditional one‐dimensional (1D) and three‐dimensional (3D) network macromolecules, the synthesis of 2D structures prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 96 publications
(211 reference statements)
0
3
0
Order By: Relevance
“…The top-down stripping method exploits shear forces to destroy interlayer van der Waals interactions following mechanical methods or using ion/molecular inserts. [48] Although the exfoliation method can yield high-quality 2D crystals, it is challenging to realize large-scale exfoliation using this method. The time inefficiency of the process also hinders the application prospects of the method.…”
Section: Top-down Stripping and Eroding Methodsmentioning
confidence: 99%
“…The top-down stripping method exploits shear forces to destroy interlayer van der Waals interactions following mechanical methods or using ion/molecular inserts. [48] Although the exfoliation method can yield high-quality 2D crystals, it is challenging to realize large-scale exfoliation using this method. The time inefficiency of the process also hinders the application prospects of the method.…”
Section: Top-down Stripping and Eroding Methodsmentioning
confidence: 99%
“…Oil spills on seas have had devastating and long-term impacts on the aquatic environment and have caused severe damage to water sources, usually injuring and killing thousands of species. An urgent problem to be addressed is the remediation of waters and environments polluted by oil leaks. , In recent years, the various methods for treating oil and water pollutants have included skimming, gravity separation, filtration, chemical dispersion, biodegradation, and absorption. , Due to their low absorption costs, eco-friendliness, and ease of operation, these methods have attracted a substantial amount of attention from researchers, and they have achieved good results. At present, the adsorption materials used for oil absorption can be divided into inorganic mineral materials, organic crop materials, and synthetic organic products. Among the synthetic organic materials, nanoporous polymers are considered to be optimal adsorption materials. , They achieve oil absorption and oil–water separation with high separation efficiencies and no secondary pollutants as a result of the porosity of the polymers. Different processing methods have been adopted to prepare nanoscale pores, including expansion and electrospinning .…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) materials with sheetlike structures and atomic level thickness have been widely used in energy-related fields due to their superior properties such as high mechanical flexibility, high specific surface area, abundant surface chemistry, and rich chemical modification characteristics. Among them, the emerging 2D polymers (2DPs) with internal periodic and areal repeat units have attracted considerable attention in recent years as they possess particular properties, such as being lightweight and having good flexibility, adjustable porous structure, high adaptability, and rich functional groups. Benefiting from these promising properties, 2DPs have shown great potential in developing advanced and stable Li metal anodes, which are attracting much interest and becoming research hot spots recently. Although there are some review articles regarding the energy storage applications of 2DPs, , a comprehensive review specialized in the advances of 2DPs in Li metal anodes has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%